Imogen or Innogen – Concerning One Conjecture of Shakespeare’s "Cymbeline’s" Oxford Publication - Elguja Khintibidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2015)
The principal novelty of the last decade in Rustaveli Studies, revealing the fact that the love story of the main characters in the MPS – Nestan and Tariel was used as a plot source in early 17th century English dramaturgy, has become a frequent topic of The Kartvelologist’s publications (The Kartvelologist, #14, 15, 16, 19, 20). One theme, pointed out in these publications, a parallel study of the main literary characters of the MPS and Cymbeline , has prompted me to realize the significance of those symbolic meanings, which, in certain cases, were used by the great playwright when selecting the names of his characters. From this point, the name of the king’s only daughter Imogen , being the protagonist of Cymbeline , is also worth noting. The present study is dedicated to the interpretation of the symbolic meaning of the name Imogen as well as the acceptability of its modified version – Innogen in some publications of the play.